To rearrange the formula for the area of a trapezoid, \( A = \frac{1}{2}h(b_1 + b_2) \), to solve for \( h \), follow these steps:
-
Start with the original formula: \[ A = \frac{1}{2}h(b_1 + b_2) \]
-
Multiply both sides by 2 to eliminate the fraction: \[ 2A = h(b_1 + b_2) \]
-
Now, divide both sides by \( (b_1 + b_2) \) to solve for \( h \): \[ h = \frac{2A}{b_1 + b_2} \]
Comparing this derived formula with the given options, the correct answer is: \[ h = \frac{2A}{b_1 + b_2} \]
None of the listed options directly match this formula. If you recheck, you may find that the second option seems to be incorrectly formatted but is what you would use to find \( h \).
So, the formula you need is: \[ h = \frac{2A}{b_1 + b_2} \]